ANALISIS DIDAKTIS DAN IDEOLOGIS TERHADAP TOKOH-TOKOH MANUSIA MUTAN DALAM KARYA FIKSI (FILM) - Dian Swandayani (LITERA, 2010)
This study aims to investigate two movies, Spider Man and Hulk, in terms of: (1) the mutant characters, (2) the background and effects experienced by the main characters, (3) the educational values, and (4) the hidden ideologies. The data sources were the two movies. The data were collected through intensive reading. The results show that the characters, Spider Man and Hulk, are heroes according to children. A mutant is defined as a genetic change concept. Peter, the main character in Spider Man, had a DNA change while Bruce in Hulk had an RNA change. The mutant theory is thought of as thinking development by evolution thinkers (Darwinians). It says that an evolution is something inevitable to achieve a better condition and happens randomly. The strong living things (including human beings) will survive through the natural selection, but the weak ones will perish.